Pengaruh Efektivitas Penggunaan Dana Kur dan Intellectual Capital Terhadap Kinerja Usaha Mikro Kecil dan Menengah (Studi Pada UMKM Pengguna Dana KUR se Kabupaten Buleleng) - Komang Tri Yasrawan; Nyoman Trisna Herawati (Jurnal Akuntansi Profesi, 2022)
This study aimed to determine the effect of effectivity of KUR use, structural capital, human capital, and customer capital toward the performance of UMKM users of KUR funds throughout Buleleng Regency individually or together. The method used in this study was quantitative with primary data obtained from questionnaire. The population of this study was 21.577 UMKM users of KUR funds throughout Buleleng Regency which were listed in Disdagperinkopukm Buleleng Regency. The sample was determined by using Isaac and Michael technique to obtain a sample of 347 UMKM. The data were collected through a questionnaire distributed online in the form of google forms and processed by multiple linear regression analysis tests using SPSS version 25. This study indicated that the effectivity of KUR use, structural capital, human capital, and customer capital individually and together affect the performance of UMKM users of KUR funds throughout Buleleng Regency positively and significantly.